2017
DOI: 10.1111/2041-210x.12910
|View full text |Cite
|
Sign up to set email alerts
|

A new framework for analysing automated acoustic species detection data: Occupancy estimation and optimization of recordings post‐processing

Abstract: The development and use of automated species detection technologies, such as acoustic recorders, for monitoring wildlife are rapidly expanding. Automated classification algorithms provide cost‐ and time‐effective means to process information‐rich data, but often at the cost of additional detection errors. Appropriate methods are necessary to analyse such data while dealing with the different types of detection errors. We developed a hierarchical modelling framework for estimating species occupancy from automat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
98
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(100 citation statements)
references
References 37 publications
2
98
0
Order By: Relevance
“…Reviewing all apparent detections is onerous and unnecessary for most applications; Chambert et al. () concluded that review of as little as 1% of apparent detections could yield unbiased and reasonably precise estimates of site occupancy, provided that researchers employ a modeling approach that explicitly accounts for false detections.…”
Section: Methodsmentioning
confidence: 99%
“…Reviewing all apparent detections is onerous and unnecessary for most applications; Chambert et al. () concluded that review of as little as 1% of apparent detections could yield unbiased and reasonably precise estimates of site occupancy, provided that researchers employ a modeling approach that explicitly accounts for false detections.…”
Section: Methodsmentioning
confidence: 99%
“…An extreme example of over‐dispersion occurs when counts are not actual individuals but signals (e.g. scat samples or bird calls) clumped around the locations of individuals (Chambert, Waddle, Miller, Walls, & Nichols, ).…”
Section: What Has Been Done So Far?mentioning
confidence: 99%
“…Due to constraints on signal-to-noise ratio (see also Darras et al 2016, Chambert et al 2018, automated methods are most likely to observe species from the foreground, rather than the background of audio recordings. Due to constraints on signal-to-noise ratio (see also Darras et al 2016, Chambert et al 2018, automated methods are most likely to observe species from the foreground, rather than the background of audio recordings.…”
Section: Bioacoustics Offer Useful Descriptors Of Community Structurementioning
confidence: 99%
“…This is because different species are differently detectable, as influenced by their behavior and vocal characteristics (Alldredge et al 2007, Pacifici et al 2008, Luther 2009, Robert et al 2012. the observation process (Darras et al 2016, Chambert et al 2018. We stress that this is a question different from that of physical presence/absence of a potentially Table 1.…”
Section: Bioacoustics Offer Useful Descriptors Of Community Structurementioning
confidence: 99%